Evaluating factors that influenced the successful implementation of an evidence-based neonatal care intervention in Chinese hospitals using the PARIHS framework - Yue, J; Liu, J; Zhao, Y; Williams, S; Zhang, B; Zhang, L; Zhang, Q; Liu, X; Wall, S; Zhao, G (BioMed Central, 2022)
Background: Evidence based interventions (EBIs) can improve patient care and outcomes. Understanding the process for successfully introducing and implementing EBIs can inform effective roll-out and scale up. The Promoting Action on Research Implementation in Health Services (PARIHS) framework can be used to evaluate and guide the introduction and implementation of EBIs. In this study, we used kangaroo mother care (KMC) as an example of an evidence-based neonatal intervention recently introduced in selected Chinese hospitals, to identify the factors that influenced its successful implementation. We also explored the utility of the PARIHS framework in China and investigated how important each of its constructs (evidence, context and facilitation) and sub-elements were perceived to be to successful implementation of EBIs in a Chinese setting.